Are illness perception and coping style associated with the delay between symptom onset and the first general practitioner consultation in early rheumatoid arthritis management? An exploratory study within the CareRA trial. (3rd May 2016) - Van der Elst, K; De Cock, D; Vecoven, E; Arat, S; Meyfroidt, S; Joly, J; Moons, P; Verschueren, P; Westhovens, R; CareRA study group,
Abstract : Objectives : Persons who are later diagnosed with early rheumatoid arthritis (ERA) often delay their first contact with a health professional after symptom onset. Besides initial symptoms, psychosocial characteristics of individuals may influence their help-seeking behaviour. We explored the role of disease characteristics, illness perception, and coping in patient-related delay before treatment initiation in recently diagnosed patients with ERA. Method : This exploratory, cross-sectional study included 112 patients with ERA from the Care for early RA (CareRA) trial for whom complete data on patient-related delay, coping, and illness perception were available. In addition to baseline sociodemographic and clinical data, the patients' psychosocial profiles were assessed with the Utrecht Coping List (UCL) and the revised Illness Perception Questionnaire (IPQ-R). Correlations were measured by Spearman's rho. Using regression analyses, we weighted the association of variables with patient-related delay. Results : Patient-related delay was positively correlated with perceptions of causality including psychological attributions (r = 0.301, p = 0.001), risk factors (r = 0.189, p = 0.045), immunity (r = 0.261, p = 0.005), and passive coping (r = 0.222, p = 0.018). It was negatively correlated with the 28 swollen joint count (SJC28; r = −0.194, p = 0.040), perceptions of treatment control (r = −0.271, p = 0.004), and illness coherence (r = −0.208, p = 0.028). Clinical and psychosocial variables explained 15% and 18%, respectively, of the variability in patient-related delay. Conclusions : Aside from a lower SJC, a longer patient-related delay was correlated with a passive coping style, a strong conviction of symptom causality, poor expected treatment control, and a feeling of limited illness coherence. Psychosocial aspects influence individuals' help-seeking behaviour and are worth considering when aiming for a reduction in ERA treatment delay.